2016
DOI: 10.15187/adr.2016.11.29.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Developing Usage Guidelines for a Card-Based Design Tool

Abstract: Background Card-based design tools have gained popularity as a means to communicate research insights and to make them usable in a design process. There are various examples of card tools and guidelines for developing a card set itself, yet there has been little research into how the usage of card tools can be systematically formulated. Although the existing literature on card tools often presents certain usages, it rarely explicates how the usage was structured, and provides few references to the underlying d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 13 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Here, a study of another card-based design tool indicated while there are designers who can immediately use the cards freely, there are also designers who needed instruction to get started, and most designers are something in between. They can explored usage by themselves but they felt unsure of their approaches without any guidances [37]. In order for most designers to use the tool efficiently, this paper aim to provide them a usage guideline based on the successful approaches carried by professional designers.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, a study of another card-based design tool indicated while there are designers who can immediately use the cards freely, there are also designers who needed instruction to get started, and most designers are something in between. They can explored usage by themselves but they felt unsure of their approaches without any guidances [37]. In order for most designers to use the tool efficiently, this paper aim to provide them a usage guideline based on the successful approaches carried by professional designers.…”
Section: Introductionmentioning
confidence: 99%
“…Lucero et al (2016) observed and reported how designers used three types of inspiration cards (PLEX, Inspiration Card, and Video Card Game) in workshops [25]. Yoon et al (2016) also conducted workshops and observed how designers used The ability to read minds or transmit information to another mind Extra-Sensory Perception The ability to perceive information without using physical senses e.g. X-ray vision, predictions Telekinesis…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations